2015
DOI: 10.1152/ajpregu.00001.2015
|View full text |Cite
|
Sign up to set email alerts
|

Construction and use of a zebrafish heart voltage and calcium optical mapping system, with integrated electrocardiogram and programmable electrical stimulation

Abstract: Zebrafish are increasingly being used as a model of vertebrate cardiology due to mammalian-like cardiac properties in many respects. The size and fecundity of zebrafish make them suitable for large-scale genetic and pharmacological screening. In larger mammalian hearts, optical mapping is often used to investigate the interplay between voltage and calcium dynamics and to investigate their respective roles in arrhythmogenesis. This report outlines the construction of an optical mapping system for use with zebra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 33 publications
4
19
0
Order By: Relevance
“…In the present study, the origin of myocyte electrical activity was located within the SAR, in agreement with previous functional (24,34,46,49,51,60,61) and anatomical (57,60) data. The mean time for propagation of atrial excitation, as well as the atrioventricular delay, corresponded with the delay calculated from ECG-derived data and with values previously reported in other optical imaging studies of the zebrafish heart (34,35). The observed location of the initiation and spread of excitation thus conformed with the recognized pattern of normal heart activation in this species, and established a functional baseline for mapping the effects of VSN stimulation.…”
Section: Discussionsupporting
confidence: 85%
“…In the present study, the origin of myocyte electrical activity was located within the SAR, in agreement with previous functional (24,34,46,49,51,60,61) and anatomical (57,60) data. The mean time for propagation of atrial excitation, as well as the atrioventricular delay, corresponded with the delay calculated from ECG-derived data and with values previously reported in other optical imaging studies of the zebrafish heart (34,35). The observed location of the initiation and spread of excitation thus conformed with the recognized pattern of normal heart activation in this species, and established a functional baseline for mapping the effects of VSN stimulation.…”
Section: Discussionsupporting
confidence: 85%
“…In preliminary experiments, we found that constant perfusion of the hearts during recordings resulted in increased signal noise, so we proceeded without perfusion of the hearts during the experiments. Lin et al showed that passive oxygenation through diffusion maintains the heart rate for hours after isolation, likely because the mature zebrafish heart is 3‐4 cell layers thick, which aids diffusion.…”
Section: Methodsmentioning
confidence: 99%
“…The key morphological, functional, mechanobiological, electrophysiological, metabolic, and molecular profiles, as well as many cardiac events, overlap with those in humans, including the kinome profiles, where most kinase inhibitors interact with the kinases . Moreover, the cardiac electrophysiological properties of the hearts of zebrafish larvae and adults resemble those of humans in many aspects . It is of particular importance to evaluate the pharmacological response of cardiac function in an animal model relevant to the human heart for an appropriate assessment of the safety (drug‐induced cardiotoxicity) and efficacy of drugs that target cardiovascular diseases (cardiopharmacology).…”
Section: Research Gaps Challenges Perspectives and Opportunities Tmentioning
confidence: 99%
“…423,424 Moreover, the cardiac electrophysiological properties of the hearts of zebrafish larvae and adults resemble those of humans in many aspects. 413,[425][426][427][428] It is of particular importance to evaluate the pharmacological response of cardiac function in an animal model relevant to the human heart for an appropriate assessment of the safety (drug-induced cardiotoxicity) and efficacy of drugs that target cardiovascular diseases (cardiopharmacology). Many human cardiovascular drugs have identical effects on zebrafish physiology, and numerous human cardiovascular disorders have been recapitulated in zebrafish genetic models.…”
Section: Zebrafish Modelmentioning
confidence: 99%
See 1 more Smart Citation